Comparative performance of disability measures - Scott D. Landes; Jean P. Hall; Bonnielin K. Swenor; Nastassia Vaitsiakhovich (PLoS ONE, 2025)
Researchers and federal agencies are currently discussing the best way to measure disability in US federal surveys. One idea being discussed is expanding/supplementing the question sets commonly used to capture disability status in order to better capture a broader segment of the disabled population. We used data from the 2010–2018 National Health Interview Survey to examine the performance of questions commonly used to measure disability in the US–the ACS-6 and Washington Group Short Set questions–in capturing intellectual and developmental disabilities, mental health disabilities, and physical health disabilities. We found that neither set of disability questions was sufficient to fully capture these disability statuses. We contend that current disability questions used in US population surveys must be expanded/supplemented in order to increase the inclusiveness of disability measurement, and thereby, improve efforts to reduce disparities experienced by the disabled population.